Development of Microemulsions Containing Glochidion wallichianum Leaf Extract and Potential for Transdermal and Topical Skin Delivery of Gallic Acid - Attawadee Sae Yoon; Pajaree Sakdiset (MDPI AG, 2020)
Glochidion wallichianum (GW) is a good source of antioxidants, including gallic acid, promoting its development as a microemulsion. We constructed five pseudo-ternary phase diagrams comprising isopropyl myristate (IPM), water, and surfactant mixture (Smix)-i.e., Labrasol®:HCO-40® (1:1) with Transcutol® (1:1, 2:1, 3:1), and Tween80:Span80 (3:2) with Transcutol® or propylene glycol:ethanol (1:1). Additionally, blank and GW extract-loaded microemulsions were prepared at an IPM:Water:Smix ratio of 10:30:60 (high water content) and 30:10:60 (high oil content) from each Smix. The physical characteristics, skin permeation, and disposition were evaluated. The formulations with high water content and conductivities provided higher gallic acid permeation and disposition than those with high oil content. The Smix of Labrasol®:HCO-40® (1:1) and Transcutol® (1:1) promoted the highest gallic acid permeation (enhancement ratio 1.78 ± 0.12) and was suitable for transdermal delivery. However, the 1% hydroxypropyl methylcellulose control gel, the microemulsion with Smix of Labrasol®:HCO-40® (1:1) with Transcutol® (2:1), and Smix of Tween80:Span80 (3:2) with propylene glycol:ethanol (1:1) could provide higher skin accumulation of gallic acid than that with other formulations. The microstructures, ratio of surfactant:cosurfactant, and compositions of microemulsions were found to affect the skin permeation and disposition of gallic acid and require optimization to act as transdermal or topical delivery carriers.